Dressing approach to the nonvanishing boundary value problem for the AKNS hierarchy - Gomes, J. F. [UNESP]; Franca, Guilherme S. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Iop Publishing Ltd, 2012)
We propose an approach to the nonvanishing boundary value problem for integrable hierarchies based on the dressing method. Then we apply the method to the AKNS hierarchy. The solutions are found by introducing appropriate vertex operators that takes into account the boundary conditions.